Is sustainability challenging in Indonesia’s energy provision? Fuel type vs. externalities in electricity cost analysis - Novena Damar Asri; Purnomo Yusgiantoro (Sustinere: Journal of Environment and Sustainability, 2021)
This study aims to reveal the challenging sustainability within Indonesia’s energy provision by studying the electricity generating cost (GC) formation, externalities’ effect, and current Indonesia’s electricity and budget condition. In studying GC formation, two variables thought to have remarkable influence are fuel price (represented by Fuel Cost/FC) and operating time, which indicates the power plant’s type (represented by Capacity Factor/CF). The regression results indicate that CF has a greater impact on GC than FC; GC increases as FC increases but decreases as CF increases. FC contributes by 10%-86% of GC, subject to fuel prices and CF. Since coal is the cheapest, GCCoal < GCGas < GCDiesel, but internalizing the externalities triples the GCCoal and doubles the GCDiesel. However, its internalization is challenging as it affects the producers’ and consumers’ welfare. Sustainable energy provision is challenging due to two factors. First, there is a dilemma between applying sustainability principles and providing energy immediately. The fastest route, which is the lowest price orientation, is preferable, indicated by coal domination in the electricity mix. Second, sustainability is not the priority yet, indicated by the environment programs is outside the top ten priority development programs.